Kesetaraan Gender dan Emansipasi Perempuan dalam Pendidikan Islam - Abidin, Zainal (Institut Agama Islam Negeri (IAIN) Metro, 2015)
The Islamic education have relationship with the gender movement because in global isues, especialy in the modern era, both of them was influenced for many thinker of muslim activies on the world. In the fact the construct of the Islamic eeducation philosophy was developed from the al-Qur’an and Hadits but the gender movement its construct from West discourse. And implicatipon of that different perspective made every one have the liberation to derminated them live for every human being. No bondaires of rule between man and women in Gender of West. For this perspectives many women emansipation movement was introduced the liberation all out of woman rules and they were be come the anti violence of the marital or family, but in now days the construct of that program of emansipation in the West is becaming the liberation and anti dogma of religion. So that its must be rethingking about the spririt of feminism was be influenced by Islamic values, especially for the moslem activities of genders. Its very importance to rekonstruct and rethingking abaout the fundamental of Islamic perspectives, because Islam as a religion teached for every muslim about the universal view and the way of life for every moslem in education between man and women are same of others aspects and the gender must be influenced by Islamic spiritual, especeialyy in education rule for moslem all aroun the world.